Pharmacology, Physiology and Genetics of the Neuropeptide S System - Rainer K. Reinscheid; Chiara Ruzza (MDPI AG, 2021)
The Neuropeptide S (NPS) system is a rather 'young' transmitter system that was discovered and functionally described less than 20 years ago. This review highlights the progress that has been made in elucidating its pharmacology, anatomical distribution, and functional involvement in a variety of physiological effects, including behavior and immune functions. Early on, genetic variations of the human NPS receptor (NPSR1) have attracted attention and we summarize current hypotheses of genetic linkage with disease and human behaviors. Finally, we review the therapeutic potential of future drugs modulating NPS signaling. This review serves as an introduction to the broad collection of original research papers and reviews from experts in the field that are presented in this Special Issue.